Logarithmic strain model for nonlinear load cell - Hong, Young Dae; Lee, Bumjoo (Sensors (Switzerland), 2019)
General load cells have typically constant sensitivity throughout the measurement range, which is acceptable for common force measurement systems. However, it is not adequate for high-performance control and high-stroke applications such as robotic systems. It is required to have a higher sensitivity in a small force range than that in a large force range. In contrast, for large loading force, it is more important to increase the measurement range than the sensitivity. To cope with these characteristics, the strain curve versus the force measurement should be derived as a logarithmic graph. To implement this nonlinear nature, the proposed load cell is composed of two mechanical components: An activator, which has a curved surface profile to translocate the contact point, and a linear torque measurement unit with a moment lever to measure the loading force. To approximate the logarithmic deformation, the curvature of the activator was designed by an exponential function. Subsequent design parameters were optimized by an evolutionary computation.
Keywords: Design parameters; High performance control; Logarithmic deformation; Logarithmic strain; Measurement range; Measurement system; Mechanical components; Nonlinear load; Force measurement; Logarithmic strain model; Nonlinear load cell